Complete Version - Prof. Banke Ogunlana, Editor-in-Chief; Edwin O. Agbaike, Managing Editor: (Covenant Journal of Physical and Life Sciences, 2019)
© 2019, Covenant University Journals All rights reserved. No part of this publication may be reproduced, stored in a retrieval system or transmitted in any form or by any meams, electronic, electrostatic, magnetic tape, mechanical, photocopying, recording or otherwise, without the prior written permission of the publisher. It is a condition of publication in this journal that manuscripts have not been published or submitted for publication and will not be submitted or published elsewhere. Upon the acceptance of articles to be published in this journal,the author(s) are required to transfer copyright of the article to the publisher.